The Racial School Climate Gap: Within‐School Disparities in Students' Experiences of Safety, Support, and Connectedness. Issue 3 (16th September 2015) - Voight, Adam; Hanson, Thomas; O'Malley, Meagan; Adekanye, Latifah
Abstract: This study used student and teacher survey data from over 400 middle schools in California to examine within‐school racial disparities in students' experiences of school climate. It further examined the relationship between a school's racial climate gaps and achievement gaps and other school structures and norms that may help explain why some schools have larger or smaller racial disparities in student reports of climate than others. Multilevel regression results problematized the concept of a "school climate" by showing that, in an average middle school, Black and Hispanic students have less favorable experiences of safety, connectedness, relationships with adults, and opportunities for participation compared to White students. The results also show that certain racial school climate gaps vary in magnitude across middle schools, and in middle schools where these gaps are larger, the racial achievement gap is also larger. Finally, the socioeconomic status of students, student–teacher ratio, and geographic location help explain some cross‐school variation in racial climate gaps. These findings have implications for how school climate in conceptualized, measured, and improved.